Objective Anthropic Reason and Culture - Czarnocka, Małgorzata (Sensus Historiae, 2024)
In my article, I consider Horkheimer’s conception of objective anthropic reason (mankind’s collective wisdom), and Durkheim’s concept of collective consciousness, related to it. I propose a slightly different concept of objective anthropic reason, namely the triad (lying in the sphere of consciousness as well as unconsciousness): basic knowledge, methods, cognitive and action values. The conditions and importance of the universality of this reason are demonstrated.